Comparison of Thermal Comfort Condition of Naturally Ventilated Courtyard, Semi-Outdoor and Indoor Air Conditioned Spaces in Tropical Climate - Allah, Mohammad Zaraa; Harir, Azian; Mohamed Kamar, Haslinda (semarak ilmu, 2023)
Universiti Tun Hussein Onn Malaysia (UTHM) elibrary is in the hot and humid tropical climate of Malaysia and has a distinctive feature of a circular courtyard and semi-outdoor spaces for practical public spaces and energy saving. This study was conducted on the ground level of the library which consists of an open terrace consisting of a cafeteria, a garden in the circular courtyard, and an air-conditioned seminar room. This study aimed to compare the thermal comfort condition of these spaces through physical and subjective measurements. Physical measurement was conducted for air temperature, relative humidity, air velocity and mean radiant temperature at the two selected sampling points on each investigated area positioned at 0.6 meters from the floor. Data were collected for three days in each area during two periods of time; 9 to 11 am and 2 to 4 pm. Subjective measurements were also collected through the distributed questionnaire to 150 respondents to determine the thermal sensation votes (TSV) of each investigated area. Calculations based on physical measurement showed the thermal comfort for both the cafeteria and garden were within 90% thermal comfort acceptability limit. PMV value for the air-conditioned seminar room was -0.45 with a PPD value of 9.03%. Both results complied with the ASHRAE 55 Standards for the acceptable condition for both naturally and air-conditioned spaces. The regression analysis showed that the comfort air temperature range based on the human response method for semi-outdoor spaces and indoor spaces were 24.8 0C to 29.0 0C and 20 0C to 23.5 0C respectively. The PMV regression analysis showed that the comfort air temperature range for indoor space was 22.4 0C to 23.5 0C. Results of the study showed that respondents perceived a higher comfort temperature range in the courtyard and cafeteria compared to indoor airconditioned spaces, but still within the recommended range of ASHRAE 55 standard. The results of the study concluded that semi-outdoor places can potentially be designed as practical public spaces for comfortable and sustainable spaces.